The Thingumajig book of health and safety - Keller, Irene; Keller, Dick (Chicago, Ill. : Childrens Press, 1982)
Learn good rules for health and safety by seeing all of the wrong things that the Thingumajigs do.
Keywords: Health -- Stories; Safety education -- Stories